Niosąc w przyszłość dziedzictwo pontyfikatu. Związki watykańskiej Fundacji Jana Pawła II z instytucjami w Polsce - Andrzej Dobrzyński (Polonia Sacra)
The John Paul II Foundation is an organization of Polish emigrants from around the world who want to be linked to the Pontificate of their compatriot. The Foundation was established by John Paul II, October 16th, 1981 in the Vatican. The purpose of the Foundation was to develop a relationship between the Holy See and Polish nation, enhance the Christian and Polish culture throughout the world, and document the Pontificate of John Paul II.